The Beginner Voters Perspectives About Political Participation Nearing 2024 Elections In SMAN 3 Takalar - Herman, Herman; Ririn Nurfaathirany Heri; Kurnia Ali Syarif (International Journal of Education, Vocational and Social Science, 2023)
This study specifically look at, analyze, and describe the viewpoint of beginner voters at SMAN 3 Takalar with regard to political participation in advance of the 2024 election. It will also look at how much knowledge first-time voters have about exercising their voting rights in advance of the 2024 election and how that knowledge relates to what factors encourage and discourage political participation. The research method utilized in this study to explore the issues is a sort of normative legal research This study is descriptive-analytical in nature. This research is descriptive in nature since it takes the form of an explanation and seeks to fully describe the legal situation. The statutory approach and the case approach were utilized as the research methods in this study. The results of the study show that: 1) still many students in SMAN 3 Takalar who still do not know the meaning of political participation and what to do in exercising and using the right to vote due to lack of socialization and information related to his position as a beginner voter. 2) Factors that can influence the involvement of a novice voter in expressing himself in the election are: awareness of the importance of the right to vote and his obligation to give the best representative to represent himself, then there is an incentive for a newbie voter to use his right of vote either from the mass media and others, and lastly political factors and the environment in which he lives. The Conclusion is Views on political engagement among first-time voters at SMAN 3 Takalar are thought to be lacking as a result of a lack of knowledge and socialization regarding the significance of exercising one's right to vote and taking part in the success of political contestation prior to the 2024 election. This is due to a lack of awareness and stimulation of the desire to engage in democratic parties as well as a lack of knowledge regarding the repercussions of failing to exercise one's right to vote